Composite alkaline hydrogen evolution electrode, preparation method thereof and water electrolysis device

By using a combination of porous metal substrate, V-VI compound semiconductor layer and transition metal chalcogenide layer in the electrolytic water electrode, the existing nickel-molybdenum-based electrode has been solved, and the efficient hydrogen gas has been achieved Made of electrolytic water, it has high catalytic activity and high temperature and alkali resistance, and is suitable for industrial production.

CN119287440AActive Publication Date: 2025-01-10CHANGCHUN UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411685104.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-10
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing nickel-molybdenum-based electrolytic water electrode process has cumbersome steps and poor catalytic effect, which hinders the commercial application of hydrogen electrolytic water preparation.

Method used

The composite alkali hydrogen evolution electrode is adopted, including a laminated porous metal substrate, a V-VI compound semiconductor layer and a transition metal chalcogen compound layer, and is prepared by a two-step hydrothermal method to form high catalytic activity and high temperature and alkali resistance. electrode.

Benefits of technology

The roughness and electrochemically active surface area of ​​the electrode surface are achieved, the catalytic activity of the hydrogen evolution reaction is improved, the process is simplified, and the process is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287440A_ABST
    Figure CN119287440A_ABST
Patent Text Reader

Abstract

The invention provides a composite alkaline hydrogen evolution electrode, a preparation method thereof and a water electrolysis device, and relates to the field of electrodes for water electrolysis. The composite alkaline hydrogen evolution electrode comprises a porous metal substrate, a V-VI group compound semiconductor layer and a transition metal chalcogenide layer which are stacked. The porous metal substrate, the V-VI group compound semiconductor layer and the transition metal chalcogenide layer are combined to serve as the electrode, the surface roughness of the electrode and the electrochemical activity surface area of the electrode are increased, and the electrode has high hydrogen evolution reaction catalytic activity. In addition, the electrode provided by the invention also has relatively high high temperature resistance and strong alkali resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrodes for water electrolysis, and in particular to a composite alkaline hydrogen evolution electrode and a preparation method thereof, and a water electrolysis device. Background Art

[0002] Hydrogen is a clean and non-polluting energy source. Water electrolysis is considered to be one of the simplest and most efficient methods for producing hydrogen, powered by renewable energy such as solar energy, wind energy, and wave energy. The free energy of hydrogen adsorption (ΔG) on the surface of noble metal Pt is H * ) is close to zero and has good conductivity, making it the best hydrogen evolution electrode. However, the high price, high cost and low reserves have greatly hindered the commercial application of Pt-based electrodes. Therefore, the development of low-cost, low overpotential and long-term stable non-precious metal electrode materials is crucial for the electrolysis of water to produce hydrogen.

[0003] The existing nickel-molybdenum-based water electrolysis electrodes have the problems of complicated process steps and poor catalytic effect. Summary of the invention

[0004] The purpose of the present application is to provide a composite alkaline hydrogen evolution electrode and a preparation method thereof and a water electrolysis device to solve the above problems.

[0005] To achieve the above objectives, this application adopts the following technical solutions:

[0006] A composite alkaline hydrogen evolution electrode comprises a porous metal substrate, a V-VI group compound semiconductor layer and a transition metal sulfide compound layer which are stacked.

[0007] According to an embodiment of the present application, the porous metal substrate includes any one of foamed molybdenum nickel, foamed iron, foamed copper, and foamed nickel.

[0008] According to an embodiment of the present application, the material forming the V-VI group compound semiconductor layer includes any one of Sb2Te3, Sb2Se3, Sb2S3, Bi2Te3, Bi2Se3, and Bi2S3;

[0009] And / or, the thickness of the Group V-VI compound semiconductor layer is 0.5 to 2 μm.

[0010] According to an embodiment of the present application, the material forming the transition metal chalcogenide compound layer includes any one of MoS2, MoSe2, SnSe2, and WS2;

[0011] And / or, the transition metal chalcogenide compound layer has a thickness of 1 to 2.5 μm.

[0012] The present application also provides a method for preparing the composite alkaline hydrogen evolution electrode as described above, comprising:

[0013] Mixing a porous metal substrate, a V-VI group compound semiconductor precursor, and water, and performing a first hydrothermal reaction in a reactor to obtain a porous metal substrate carrying a V-VI group compound semiconductor layer;

[0014] The porous metal substrate carrying the V-VI group compound semiconductor layer, the transition metal sulfide compound precursor and water are mixed, and a second hydrothermal reaction is carried out in a reaction kettle to obtain a composite alkaline hydrogen evolution electrode.

[0015] According to an embodiment of the present application, the V-VI group compound semiconductor precursor includes a substance containing a group V element and a substance containing a group VI element, the substance containing the group V element includes any one of an antimony source and a bismuth source, and the substance containing the group VI element includes a tellurium source;

[0016] And / or, the antimony source includes at least one of potassium antimony tartrate, antimony trichloride, and antimony oxide, the tellurium source includes at least one of sodium tellurate, potassium tellurate, tellurium powder, and tellurium oxide, and the bismuth source includes Bi2O3;

[0017] and / or, the molar ratio of the substance containing the group V element to the substance containing the group VI element is 1:(3-4.5);

[0018] And / or, when the substance containing group V elements includes an antimony source, when the first hydrothermal reaction is performed, the method further includes adding glucose and ethylenediamine to the reaction system, wherein the molar ratio of the antimony source to the glucose is 1:(14-16); the content ratio of the antimony source to the ethylenediamine is 0.135:(18-22) g / ml;

[0019] And / or, when the substance containing group V elements includes a bismuth source, when the first hydrothermal reaction is carried out, the method also includes adding PVP and sodium hydroxide to the reaction system, the mass ratio of the bismuth source to the PVP is 0.233:(0.4-0.6), and the molar ratio of the bismuth source to the sodium hydroxide is 1:(18-22).

[0020] According to an embodiment of the present application, the temperature of the first hydrothermal reaction is 170-190°C;

[0021] And / or, the time of the first hydrothermal reaction is 11-24 hours.

[0022] According to an embodiment of the present application, the transition metal chalcogenide compound precursor includes a molybdenum source and a sulfur source;

[0023] And / or, the molybdenum source includes at least one of ammonium molybdate and sodium molybdate, and the sulfur source includes at least one of thioacetamide and thiourea;

[0024] and / or, the molar ratio of the molybdenum source to the sulfur source is 1:(2.1-2.7);

[0025] and / or, the molar ratio of the antimony source to the molybdenum source is 1:(8-9);

[0026] And / or, the concentration of the molybdenum source in the reaction system is 0.04-0.08 mol / L.

[0027] According to an embodiment of the present application, the temperature of the second hydrothermal reaction is 170-190°C;

[0028] And / or, the time of the second hydrothermal reaction is 19-21 hours.

[0029] The present application also provides a water electrolysis device, which includes a cathode and an anode, and the cathode includes the composite alkaline hydrogen evolution electrode described above or includes the composite alkaline hydrogen evolution electrode prepared by the preparation method described above.

[0030] Compared with the prior art, the beneficial effects of this application include:

[0031] The present application uses a combination of a porous metal substrate, a V-VI group compound semiconductor layer, and a transition metal sulfide compound layer as an electrode, which increases the roughness of the electrode surface and the electrochemically active surface area of ​​the electrode. The electrode of the present application has a high catalytic activity for hydrogen evolution reaction. Moreover, the electrode of the present application has a hierarchical heterogeneous structure, so that the electrode of the present application has a high catalytic activity. In addition, the electrode of the present application also has high resistance to high temperature and strong alkali.

[0032] The present invention only requires two steps of hydrothermal method to prepare an electrode with high catalytic activity. The method of the present invention has the advantages of simple process, easy process control and short cycle, which is conducive to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0034] Figure 1 A schematic diagram of the structure of the composite alkaline hydrogen evolution electrode prepared in Example 1;

[0035] Figure 2 This is a SEM image of the composite alkaline hydrogen evolution electrode prepared in Example 1;

[0036] Figure 3 This is a SEM image of the layered structure of the composite alkaline hydrogen evolution electrode prepared in Example 1;

[0037] Figure 4 LSV curve of the composite alkaline hydrogen evolution electrode prepared in Example 1;

[0038] Figure 5 LSV curve of MoS2-Bi2Te3@NMF prepared in Example 2;

[0039] Figure 6 This is a SEM image of the raw material foam molybdenum nickel NMF of Comparative Example 1;

[0040] Figure 7 is the SEM image of Sb2Te3@NMF prepared in Comparative Example 1;

[0041] Figure 8 is the LSV curve of Sb2Te3@NMF prepared in comparative example 1;

[0042] Fig. 9 LSV curve of MoS2@NMF prepared in Comparative Example 2;

[0043] Fig.10 LSV curve of Sb2Te3-MoS2@NMF prepared in Comparative Example 3;

[0044] Fig.11 This is the SEM image of MoS2-Sb2Te3@NMF-2 prepared in Comparative Example 4;

[0045] Fig.12 LSV curve of MoS2-Sb2Te3@NMF-2 prepared in Comparative Example 4;

[0046] Fig.13 This is the SEM image of MoS2-Sb2Te3@NMF-3 prepared in Comparative Example 5;

[0047] Fig.14 LSV curve of MoS2-Sb2Te3@NMF-3 prepared in Comparative Example 5;

[0048] Fig.15 The figure is a comparison diagram of the hydrogen evolution overpotential of the electrodes prepared in Example 1, Comparative Example 4 and Comparative Example 5;

[0049] Fig.16 It is a comparison diagram of electrochemical impedance spectroscopy (EIS) of electrodes prepared from NMF, Example 1 and Comparative Examples 1-3;

[0050] Fig.17 It is a comparison diagram of polarization curves of electrodes prepared from NMF, Example 1 and Comparative Examples 1-3;

[0051] Fig.18It is a comparison diagram of Tafel curves of electrodes prepared from NMF, Example 1 and Comparative Examples 1-3;

[0052] Fig.19 This is the chronopotentiometry curve of the composite alkaline hydrogen evolution electrode prepared in Example 1. DETAILED DESCRIPTION

[0053] As used herein:

[0054] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0055] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0056] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0057] In these examples, parts and percentages are by mass unless otherwise indicated.

[0058] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0059] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0060] The present application provides a composite alkaline hydrogen evolution electrode, which comprises a porous metal substrate, a V-VI group compound semiconductor layer, and a transition metal sulfide compound layer which are stacked.

[0061] According to an embodiment of the present application, the porous metal substrate includes any one of foamed molybdenum nickel, foamed iron, foamed copper, and foamed nickel.

[0062] According to some embodiments of the present application, the number of pores of the porous metal substrate is 13-120 PPI, wherein each end value of the number of pores may allow a deviation of ±5 to ±10; the surface density of the porous metal substrate is 280-300 g / m 2 , wherein each endpoint value of the surface density may allow a deviation of ±30; the thickness of the porous metal substrate is 0.5 to 10 mm, wherein each endpoint value of the thickness may allow a deviation of ±0.05 to ±1.0.

[0063] The number of pores of the porous metal substrate used in the examples of the present application is 13-120 PPI, and the surface density of the porous metal substrate is 280-300 g / m 2 , the thickness of the porous metal substrate is 0.5 to 10 mm.

[0064] According to an embodiment of the present application, the material forming the V-VI group compound semiconductor layer includes any one of Sb2Te3, Sb2Se3, Sb2S3, Bi2Te3, Bi2Se3, and Bi2S3;

[0065] And / or, the thickness of the Group V-VI compound semiconductor layer is 0.5 to 2 μm.

[0066] For example, the thickness of the Group V-VI compound semiconductor layer may be 0.5 μm, 1 μm, 1.5 μm, 2 μm, or any value between 0.5 and 2 μm.

[0067] According to an embodiment of the present application, the material forming the transition metal chalcogenide compound layer includes any one of MoS2, MoSe2, SnSe2, and WS2;

[0068] And / or, the transition metal chalcogenide compound layer has a thickness of 1 to 2.5 μm.

[0069] For example, the thickness of the transition metal chalcogenide layer may be 1 μm, 1.5 μm, 2 μm, 2.5 μm, or any value between 1 and 2.5 μm.

[0070] The present application also provides a method for preparing the composite alkaline hydrogen evolution electrode as described above, comprising:

[0071] Mixing a porous metal substrate, a V-VI group compound semiconductor precursor, and water, and performing a first hydrothermal reaction in a reactor to obtain a porous metal substrate carrying a V-VI group compound semiconductor layer;

[0072] The porous metal substrate carrying the V-VI group compound semiconductor layer, the transition metal sulfide compound precursor and water are mixed, and a second hydrothermal reaction is carried out in a reaction kettle to obtain a composite alkaline hydrogen evolution electrode.

[0073] According to an embodiment of the present application, the V-VI group compound semiconductor precursor includes a substance containing a group V element and a substance containing a group VI element, the substance containing the group V element includes any one of an antimony source and a bismuth source, and the substance containing the group VI element includes a tellurium source;

[0074] And / or, the antimony source includes at least one of potassium antimony tartrate, antimony trichloride, and antimony oxide, the tellurium source includes at least one of sodium tellurate, potassium tellurate, tellurium powder, and tellurium oxide, and the bismuth source includes Bi2O3;

[0075] and / or, the molar ratio of the substance containing the group V element to the substance containing the group VI element is 1:(3-4.5);

[0076] For example, the molar ratio of the substance containing the Group V element to the substance containing the Group VI element may be 1:3, 1:3.5, 1:4, 1:4.5 or any value between 1:(3-4.5).

[0077] And / or, when the substance containing group V elements includes an antimony source, when the first hydrothermal reaction is performed, the method further includes adding glucose and ethylenediamine to the reaction system, wherein the molar ratio of the antimony source to the glucose is 1:(14-16); the content ratio of the antimony source to the ethylenediamine is 0.135:(18-22) g / ml;

[0078] For example, the molar ratio of the antimony source to glucose can be any value between 1:14, 1:15, 1:16 or 1:(14-16), and the content ratio of the antimony source to ethylenediamine can be any value between 0.135:18 g / ml, 0.135:19 g / ml, 0.135:20 g / ml, 0.135:21 g / ml, 0.135:22 g / ml or 0.135:(18-22) g / ml.

[0079] And / or, when the substance containing group V elements includes a bismuth source, when the first hydrothermal reaction is carried out, the method also includes adding PVP and sodium hydroxide to the reaction system, the mass ratio of the bismuth source to the PVP is 0.233:(0.4-0.6), and the molar ratio of the bismuth source to the sodium hydroxide is 1:(18-22).

[0080] For example, the mass ratio of the bismuth source to PVP can be any value between 0.233:0.4, 0.233:0.5, 0.233:0.6 or 0.233:(0.4-0.6), and the molar ratio of the bismuth source to sodium hydroxide can be any value between 1:18, 1:19, 1:20, 1:21, 1:22 or 1:(18-22).

[0081] According to an embodiment of the present application, the temperature of the first hydrothermal reaction is 170-190°C; for example, the temperature of the first hydrothermal reaction can be 170°C, 180°C, 190°C or any value between 170-190°C.

[0082] And / or, the time of the first hydrothermal reaction is 11-24 hours. For example, the time of the first hydrothermal reaction can be 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours or any value between 11 and 24 hours.

[0083] According to an embodiment of the present application, the transition metal chalcogenide compound precursor includes a molybdenum source and a sulfur source;

[0084] And / or, the molybdenum source includes at least one of ammonium molybdate and sodium molybdate, and the sulfur source includes at least one of thioacetamide and thiourea;

[0085] The molar ratio of the molybdenum source to the sulfur source is 1:(2.1-2.7); for example, the molar ratio of the molybdenum source to the sulfur source can be 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7 or any value between 1:(2.1-2.7).

[0086] And / or, the molar ratio of the antimony source to the molybdenum source is 1:(8-9). For example, the molar ratio of the antimony source to the molybdenum source can be 1:8, 1:8.1, 1:8.2, 1:8.3, 1:8.4, 1:8.5, 1:8.6, 1:8.7, 1:8.8, 1:8.9, 1:9 or any value between 1:(8-9).

[0087] And / or, the concentration of the molybdenum source in the reaction system is 0.04-0.08 mol / L. For example, the concentration of the molybdenum source in the reaction system can be 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L or any value between 0.04-0.08 mol / L.

[0088] According to an embodiment of the present application, the temperature of the second hydrothermal reaction is 170-190°C; for example, the temperature of the second hydrothermal reaction can be 170°C, 180°C, 190°C or any value between 170-190°C.

[0089] And / or, the second hydrothermal reaction time is 19-21 hours. For example, the second hydrothermal reaction time can be 19 hours, 20 hours, 21 hours or any value between 19 and 21 hours.

[0090] The present application also provides a water electrolysis device, which includes a cathode and an anode, and the cathode includes the composite alkaline hydrogen evolution electrode described above or includes the composite alkaline hydrogen evolution electrode prepared by the preparation method described above.

[0091] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0092] Example 1

[0093] Example 1 provides a method for preparing a composite alkaline hydrogen evolution electrode MoS2-Sb2Te3@NMF-1, comprising the following steps:

[0094] a. First, cut a piece of 2cm*2cm foamed molybdenum nickel, and then place it in 1M HCl solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 15 minutes to remove oxides, oil stains and impurities on the surface of the foamed molybdenum nickel. After cleaning, the foamed molybdenum nickel is dried for later use.

[0095] b. Dissolve 0.135g potassium antimony tartrate, 0.1825g sodium telluride, 0.6g glucose and 20ml ethylenediamine in 10ml deionized water to form a uniform solution to obtain the precursor solution for the hydrothermal reaction. Add the cleaned foamed molybdenum nickel and the precursor solution to a 50mL microreactor, and then place the microreactor in an electric heated blast drying oven to react at 180°C for 12h. After the reaction, take out the foamed molybdenum nickel and wash it several times with anhydrous ethanol, then dry it for 2h, and finally obtain the foamed molybdenum nickel loaded with a three-dimensional Sb2Te3 nanoarray structure.

[0096] c. Dissolve 0.37g of ammonium molybdate and 0.335g of thioacetamide in 30ml of deionized water to form a uniform solution to obtain a precursor solution for the hydrothermal reaction. Add the foamed molybdenum nickel loaded with a three-dimensional Sb2Te3 nanoarray structure and the precursor solution into a 50mL microreactor, and then place the microreactor in an electric heated blast drying oven to react at 180°C for 20h. After the reaction, take out the foamed molybdenum nickel and wash it several times with anhydrous ethanol, then dry it for 2h, and finally obtain the foamed molybdenum nickel MoS2-Sb2Te3@NMF-1 loaded with MoS2 spherical nanostructures, which is a composite alkaline hydrogen evolution electrode.

[0097] refer to Figure 1 The composite alkaline hydrogen evolution electrode includes MoS2, Sb2Te3 and a foamed molybdenum-nickel metal carrier NMF, and MoS2 and Sb2Te3 grow uniformly on the surface of the foamed molybdenum-nickel metal carrier NMF.

[0098] The SEM of MoS2-Sb2Te3@NMF-1 prepared in Example 1 is as follows Figure 2 As shown, Figure 2 The SEM images of MoS2-Sb2Te3@NMF-1 at different magnifications are shown in Figure 2. Figure 2 It can be seen that after two-step hydrothermal treatment, the nano-spherical catalytic active material MoS2 grows evenly on the surface of the three-dimensional Sb2Te3 nanoarray. After magnification, nanospheres with a diameter of about 200nm can be observed and the growth is very dense, covering the original three-dimensional nanoarray morphology, increasing the electrochemical active surface area of ​​the electrode, and thus improving the electrocatalytic performance. Figure 3 The SEM image of the layered structure of MoS2-Sb2Te3@NMF-1 is shown in the figure. The thickness of the Sb2Te3 layer can reach 0.5 to 2 μm, and the thickness of the MoS2 layer can reach 1 to 2.5 μm.

[0099] The three-dimensional Sb2Te3 nanoarray structure in the electrode of Example 1 increases the roughness of the electrode surface, and the MoS2 nanosphere structure increases the electrochemically active surface area of ​​the electrode, which plays an important role in maintaining high catalytic activity at high current density.

[0100] In order to test the activity of its corresponding material, the electrode prepared in this application was used as the working electrode, the graphite rod and the Hg / HgO electrode were used as the counter electrode and the reference electrode, respectively, and a three-electrode system was used to carry out a hydrogen evolution reaction test (linear sweep voltammetry, LSV) in 1M KOH electrolyte at room temperature.

[0101] The LSV curve of MoS2-Sb2Te3@NMF-1 prepared in Example 1 is as follows: Figure 4 As shown in Figure 1, the MoS2-Sb2Te3@NMF-1 electrode prepared in Example 1 exhibits excellent electrocatalytic hydrogen evolution performance in a 1M KOH aqueous solution. 2 , 50mA / cm 2 , 100mA / cm 2 When the overpotentials are 2 mV, 176 mV, and 206 mV, respectively, the MoS2-Sb2Te3@NMF-1 prepared in Example 1 exhibits excellent hydrogen evolution performance.

[0102] Example 2

[0103] Example 2 provides a method for preparing a composite alkaline hydrogen evolution electrode MoS2-Bi2Te3@NMF, comprising the following steps:

[0104] a. First, cut a piece of 2cm*2cm foamed molybdenum nickel, and then place it in 1M HCl solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 15 minutes to remove oxides, oil stains and impurities on the surface of the foamed molybdenum nickel. After cleaning, the foamed molybdenum nickel is dried for later use.

[0105] b. Weigh 0.5g PVP and dissolve it in 33ml ethylene glycol, and stir continuously for 20min; weigh 0.233g Bi2O3, 0.239g TeO2, and 0.4g NaOH and add them to the stirred solution, and stir continuously for 3h to form a uniform solution to obtain the precursor liquid for the hydrothermal reaction. Add the cleaned foamed molybdenum nickel and the precursor liquid to a 50mL microreactor, and then place the microreactor in an electric blast drying oven to react at 180°C for 24h. After the reaction is completed, take out the foamed molybdenum nickel and wash it several times with anhydrous ethanol, and then dry it for 2h to finally obtain a foamed molybdenum nickel loaded with Bi2Te3 nano-layered structure.

[0106] c. Dissolve 0.37g of ammonium molybdate and 0.335g of thioacetamide in 30ml of deionized water to form a uniform solution to obtain a precursor solution for the hydrothermal reaction. Add the foamed molybdenum nickel loaded with a three-dimensional Bi2Te3 nanoarray structure and the precursor solution into a 50mL microreactor, and then place the microreactor in an electric heated blast drying oven to react at 180°C for 20h. After the reaction, take out the foamed molybdenum nickel and wash it several times with anhydrous ethanol, then dry it for 2h, and finally obtain the foamed molybdenum nickel MoS2-Bi2Te3@NMF loaded with a MoS2 nanolayered structure, which is a composite alkaline hydrogen evolution electrode.

[0107] The LSV curve of the hydrogen evolution reaction catalyzed by MoS2-Bi2Te3@NMF prepared in Example 2 in 1M KOH at room temperature is as follows: Figure 5 As shown in Figure 2, it exhibits excellent electrocatalytic hydrogen evolution performance in a 1M KOH aqueous solution. 2 , 50mA / cm 2 , 100mA / cm 2 When the overpotentials are 22 mV, 226 mV and 318 mV respectively, the MoS2-Bi2Te3@NMF prepared in Example 2 exhibits excellent hydrogen evolution performance.

[0108] Comparative Example 1

[0109] Comparative Example 1 provides a method for preparing Sb2Te3@NMF, comprising the following steps:

[0110] a. First, cut a piece of 2cm*2cm foamed molybdenum nickel, and then place it in 1M HCl solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 15 minutes to remove oxides, oil stains and impurities on the surface of the foamed molybdenum nickel. After cleaning, dry the foamed nickel for later use.

[0111] b. Dissolve 0.135g potassium antimony tartrate, 0.1825g sodium telluride, 0.6g glucose and 20ml ethylenediamine in 10ml deionized water to form a uniform solution to obtain the precursor solution for the hydrothermal reaction. Add the cleaned foamed molybdenum nickel and the precursor solution to a 50mL microreactor, and then place the microreactor in an electric blast drying oven to react at 180°C for 12h. After the reaction, take out the foamed molybdenum nickel and wash it several times with deionized water, then dry it for 2h, and finally obtain the foamed molybdenum nickel loaded with a three-dimensional Sb2Te3 nanoarray structure.

[0112] The SEM of Sb2Te3@NMF prepared in Comparative Example 1 is as follows Figure 7 As shown, Figure 7 There are two SEM images of Sb2Te3@NMF at different magnifications. Figure 7It can be seen that after the hydrothermal treatment, the three-dimensional Sb2Te3 nanoarray grows evenly on the surface of the molybdenum nickel foam. After magnification, it can be observed that the surface of the three-dimensional Sb2Te3 nanoarray is very smooth, and although it grows very densely on the surface of the molybdenum nickel foam, there are large gaps between the rods. Figure 7 and Figure 6 Comparing the SEM images of the foamed molybdenum-nickel metal substrate, it can be seen that the three-dimensional Sb2Te3 nanoarray makes the surface of NMF rougher, thereby increasing the contact area between the nanoarray and the electrolyte.

[0113] The LSV curve of the Sb2Te3@NMF electrode prepared in Comparative Example 1 catalyzing the hydrogen evolution reaction in 1M KOH at room temperature is shown in Figure 8 As shown by Figure 8 It can be seen that the electrocatalytic hydrogen evolution performance of Sb2Te3@NMF prepared in comparative example 1 in a 1M KOH aqueous solution is very good when the current density is 10 mA / cm 2 , 50mA / cm 2 When , the overpotentials are 254mV and 404mV respectively.

[0114] Comparative Example 2

[0115] Comparative Example 2 provides a method for preparing MoS2@NMF, comprising the following steps:

[0116] a. First, cut a piece of 2cm*2cm foamed molybdenum nickel, and then place it in 1M HCl solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 15 minutes to remove oxides, oil stains and impurities on the surface of the foamed molybdenum nickel. After cleaning, the foamed molybdenum nickel is dried for later use.

[0117] b. Dissolve 0.37g of ammonium molybdate and 0.335g of thioacetamide in 30ml of deionized water to form a uniform solution to obtain the precursor solution for the hydrothermal reaction. Add the cleaned foamed molybdenum nickel and the precursor solution into a 50mL microreactor, and then place the microreactor in an electric heated blast drying oven to react at 180°C for 20h. After the reaction, take out the foamed molybdenum nickel and wash it several times with anhydrous ethanol, then dry it for 2h to finally obtain the MoS2@NMF hydrogen evolution electrode.

[0118] The LSV curve of the MoS2@NMF prepared in comparative example 2 catalyzed hydrogen evolution reaction in 1M KOH at room temperature is shown in Fig. 9 As shown by Fig. 9 It can be seen that the electrocatalytic hydrogen evolution performance of MoS2@NMF prepared in Comparative Example 2 in a 1 M KOH aqueous solution is very good when the current density is 10 mA / cm 2 , 50mA / cm 2When , the overpotentials are 62mV and 208mV respectively.

[0119] Comparative Example 3

[0120] Comparative Example 3 provides a method for preparing Sb2Te3-MoS2@NMF, comprising the following steps:

[0121] a. First, cut a piece of 2cm*2cm foamed molybdenum nickel, and then place it in 1M HCl solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 15 minutes to remove oxides, oil stains and impurities on the surface of the foamed molybdenum nickel. After cleaning, the foamed molybdenum nickel is dried for later use.

[0122] b. Dissolve 0.37g of ammonium molybdate and 0.335g of thioacetamide in 30ml of deionized water to form a uniform solution to obtain a precursor solution for the hydrothermal reaction. Add the cleaned foamed molybdenum nickel and the precursor solution to a 50mL microreactor, and then place the microreactor in an electric blast drying oven to react at 180°C for 20h. After the reaction, take out the foamed molybdenum nickel and wash it several times with anhydrous ethanol, then dry it for 2h to finally obtain a foamed molybdenum nickel loaded with MoS2 nanostructures.

[0123] c. Dissolve 0.135g potassium antimony tartrate, 0.1825g sodium telluride, 0.6g glucose and 20ml ethylenediamine in 10ml deionized water to form a uniform solution to obtain the precursor solution for the hydrothermal reaction. Add the foamed molybdenum nickel loaded with MoS2 nanostructures and the precursor solution into a 50mL microreactor, and then place the microreactor in an electric heated blast drying oven to react at 180°C for 12h. After the reaction, take out the foamed molybdenum nickel and wash it several times with anhydrous ethanol, then dry it for 2h, and finally obtain the Sb2Te3-MoS2@NMF hydrogen evolution electrode.

[0124] The LSV curve of the hydrogen evolution reaction catalyzed by Sb2Te3-MoS2@NMF prepared in comparative example 3 in 1M KOH at room temperature is shown in Fig.10 As shown by Fig.10 It can be seen that the electrocatalytic hydrogen evolution performance of Sb2Te3-MoS2@NMF prepared in comparative example 3 in a 1M KOH aqueous solution is very good when the current density is 10 mA / cm 2 , 50mA / cm 2 When , the overpotentials are 118mV and 204mV respectively.

[0125] Comparative Example 4

[0126] Comparative Example 4 provides a method for preparing a composite alkaline hydrogen evolution electrode MoS2-Sb2Te3@NMF-2, comprising the following steps:

[0127] a. First, cut a piece of 2cm*2cm foamed molybdenum nickel, and then place it in 1M HCl solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 15 minutes to remove oxides, oil stains and impurities on the surface of the foamed molybdenum nickel. After cleaning, the foamed molybdenum nickel is dried for later use.

[0128] b. Dissolve 0.27g potassium antimony tartrate, 0.365g sodium telluride, 0.6g glucose and 20ml ethylenediamine in 10ml deionized water to form a uniform solution to obtain the precursor solution for the hydrothermal reaction. Add the cleaned foamed molybdenum nickel and the precursor solution to a 50mL microreactor, and then place the microreactor in an electric blast drying oven to react at 180°C for 24h. After the reaction, take out the foamed molybdenum nickel and wash it several times with anhydrous ethanol, then dry it for 2h, and finally obtain the foamed molybdenum nickel loaded with Sb2Te3 nanostructures.

[0129] c. Dissolve 0.74g of ammonium molybdate and 0.67g of thioacetamide in 30ml of deionized water to form a uniform solution to obtain a precursor solution for hydrothermal reaction. Add the molybdenum nickel foam loaded with Sb2Te3 nanostructures and the precursor solution into a 50mL microreactor, and then place the microreactor in an electric heated blast drying oven to react at 180°C for 20h. After the reaction, take out the molybdenum nickel foam and wash it with anhydrous ethanol several times, then dry it for 2h, and finally obtain the molybdenum nickel foam loaded with MoS2 nanostructures MoS2-Sb2Te3@NMF-2, which is a composite alkaline hydrogen evolution electrode.

[0130] The SEM images of the layered structure of MoS2-Sb2Te3@NMF-2 prepared in Comparative Example 4 are as follows: Fig.11 As shown, after two-step hydrothermal treatment, the thickness of the Sb2Te3 layer can reach 3-4μm, and the thickness of the MoS2 layer can reach 3-5μm.

[0131] The LSV curve of the hydrogen evolution reaction catalyzed by MoS2-Sb2Te3@NMF-2 prepared in Comparative Example 4 in 1M KOH at room temperature is as follows: Fig.12 As shown, Fig.12 It can be seen that the electrocatalytic hydrogen evolution performance in a 1M KOH aqueous solution is 2 , 50mA / cm 2 , 100mA / cm 2 When , the overpotentials are 57mV, 326mV, and 555mV respectively.

[0132] Comparative Example 5

[0133] Comparative Example 5 provides a method for preparing a composite alkaline hydrogen evolution electrode MoS2-Sb2Te3@NMF-3, comprising the following steps:

[0134] a. First, cut a piece of 2cm*2cm foamed molybdenum nickel, and then place it in 1M HCl solution, anhydrous ethanol and deionized water for ultrasonic cleaning for 15 minutes to remove oxides, oil stains and impurities on the surface of the foamed molybdenum nickel. After cleaning, the foamed molybdenum nickel is dried for later use.

[0135] b. Dissolve 0.0675g potassium antimony tartrate, 0.0913g sodium telluride, 0.6g glucose and 20ml ethylenediamine in 10ml deionized water to form a uniform solution to obtain the precursor solution for the hydrothermal reaction. Add the cleaned foamed molybdenum nickel and the precursor solution to a 50mL microreactor, and then place the microreactor in an electric heated blast drying oven to react at 180°C for 10h. After the reaction, take out the foamed molybdenum nickel and wash it several times with anhydrous ethanol, then dry it for 2h, and finally obtain the foamed molybdenum nickel loaded with Sb2Te3 nanostructures.

[0136] c. Dissolve 0.135g of ammonium molybdate and 0.17g of thioacetamide in 30ml of deionized water to form a uniform solution to obtain a precursor solution for the hydrothermal reaction. Add the molybdenum nickel foam loaded with Sb2Te3 nanostructures and the precursor solution into a 50mL microreactor, and then place the microreactor in an electric heated blast drying oven to react at 180°C for 15h. After the reaction, take out the molybdenum nickel foam and wash it with anhydrous ethanol several times, then dry it for 2h, and finally obtain the molybdenum nickel foam loaded with MoS2 nanostructures MoS2-Sb2Te3@NMF-3, which is a composite alkaline hydrogen evolution electrode.

[0137] The SEM images of the layered structure of MoS2-Sb2Te3@NMF-3 prepared in Comparative Example 5 are as follows: Fig.13 As shown, after two-step hydrothermal treatment, the thickness of the Sb2Te3 layer can reach 0.1-0.4 μm, and the thickness of the MoS2 layer can reach 0.1-0.8 μm.

[0138] The LSV curve of the MoS2-Sb2Te3@NMF-3 prepared in comparative example 5 catalyzed hydrogen evolution reaction in 1M KOH at room temperature is as follows: Fig.14 As shown, Fig.14 It can be seen that the electrocatalytic hydrogen evolution performance in a 1M KOH aqueous solution is 2 , 50mA / cm 2 When , the overpotentials are 423mV and 768mV respectively.

[0139] Example 1, Comparative Example 4 and Comparative Example 5 were respectively subjected to a current density of 10 mA / cm 2 , 50mA / cm 2 The overpotential when is compared, such as Fig.15 As shown by Fig.15It can be seen that the overpotential of the electrode of Example 1 at the same current density is significantly lower than that of Comparative Examples 4 and 5, indicating that the electrode of Example 1 has a better hydrogen evolution ability. This is because too thick and too thin two-dimensional material nanostructure layers will hinder the transfer of electrons and reduce the electrochemical active surface area. Example 1 has the lowest overpotential and the hydrogen evolution ability is better, indicating that the preferred thickness of the Sb2Te3 layer is 0.5-2μm, and the preferred thickness of the MoS2 layer is 1-2.5μm.

[0140] Electrochemical impedance spectroscopy (EIS) is mainly used to analyze and test the electrochemical impedance of materials. It is an important means to understand the catalytic performance of materials and their causes. This application conducted EIS tests on NMF, MoS2-Sb2Te3@NMF-1 prepared in Example 1, Sb2Te3@NMF prepared in Comparative Example 1, MoS2@NMF prepared in Comparative Example 2, and Sb2Te3-MoS2@NMF prepared in Comparative Example 3. The results are as follows: Fig.16 As shown. Fig.16 It can be found that NMF has the smallest electron transfer resistance (Rct) of 10.74Ω, indicating that its electron transfer rate is the fastest; while MoS2-Sb2Te3@NMF-1 has the largest Rct of 1.626E+9Ω. Despite the large Rct, the electrode MoS2-Sb2Te3@NMF-1 has highly exposed active sites that can effectively promote the generation of hydrogen.

[0141] Fig.17 Figure 2 is the polarization curve of the electrode prepared from NMF, Example 1, and Comparative Examples 1-3. It can be seen from the figure that MoS2-Sb2Te3@NMF-1 prepared in Example 1 exhibits excellent electrocatalytic hydrogen evolution performance in a 1M KOH aqueous solution. When the current density is 10 mA / cm 2 , 50mA / cm 2 , 100mA / cm 2 When the overpotential is 2mV, 176mV, and 206mV, respectively, it is obviously better than the electrodes prepared by NMF and comparative examples 1-3, and also better than the existing reported electrodes for water electrolysis.

[0142] Depend on Fig.18 It can be seen that the Tafel slope (16 mV / dec) of the MoS2-Sb2Te3@NMF-1 electrode prepared in Example 1 is smaller than the Tafel slope of the electrodes prepared in Comparative Examples 1-3, indicating that the MoS2-Sb2Te3@NMF-1 electrode prepared in Example 1 is more efficient in promoting the hydrogen evolution reaction.

[0143] The composite alkaline hydrogen evolution electrode prepared in Example 1 was subjected to a voltage-time test under high temperature and strong alkali (60°C, 6M KOH). The results are as follows: Fig.19As shown. Fig.19 It can be seen that at 50 mA cm 2 Under the current density, after 24 hours of testing, the composite alkaline hydrogen evolution electrode prepared in Example 1 has good performance stability and a relatively smooth curve. After 24 hours of testing, the overpotential increases by 50 mV, indicating that the electrode of the present application has high resistance to high temperature and strong alkali.

[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0145] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A composite alkaline hydrogen evolution electrode, characterized in that: The composite alkaline hydrogen evolution electrode comprises a porous metal substrate, a V-VI group compound semiconductor layer and a transition metal sulfide compound layer which are stacked.

2. The composite alkaline hydrogen evolution electrode according to claim 1, characterized in that: The porous metal substrate includes any one of foamed molybdenum nickel, foamed iron, foamed copper and foamed nickel.

3. The composite alkaline hydrogen evolution electrode according to claim 1, characterized in that: The material forming the V-VI group compound semiconductor layer includes any one of Sb2Te3, Sb2Se3, Sb2S3, Bi2Te3, Bi2Se3, and Bi2S3; And / or, the thickness of the Group V-VI compound semiconductor layer is 0.5 to 2 μm.

4. The composite alkaline hydrogen evolution electrode according to any one of claims 1 to 3, characterized in that: The material forming the transition metal chalcogenide compound layer includes any one of MoS2, MoSe2, SnSe2, and WS2; And / or, the transition metal chalcogenide compound layer has a thickness of 1 to 2.5 μm.

5. A method for preparing a composite alkaline hydrogen evolution electrode according to any one of claims 1 to 4, characterized in that: include: Mixing a porous metal substrate, a V-VI group compound semiconductor precursor, and water, and performing a first hydrothermal reaction in a reactor to obtain a porous metal substrate carrying a V-VI group compound semiconductor layer; The porous metal substrate carrying the V-VI group compound semiconductor layer, the transition metal sulfide compound precursor and water are mixed, and a second hydrothermal reaction is carried out in a reaction kettle to obtain a composite alkaline hydrogen evolution electrode.

6. The method for preparing the composite alkaline hydrogen evolution electrode according to claim 5, characterized in that: The V-VI group compound semiconductor precursor includes a substance containing a group V element and a substance containing a group VI element, wherein the substance containing the group V element includes any one of an antimony source and a bismuth source, and the substance containing the group VI element includes a tellurium source; And / or, the antimony source includes at least one of potassium antimony tartrate, antimony trichloride, and antimony oxide, the tellurium source includes at least one of sodium tellurate, potassium tellurate, tellurium powder, and tellurium oxide, and the bismuth source includes Bi2O3; and / or, the molar ratio of the substance containing the group V element to the substance containing the group VI element is 1:(3-4.5); And / or, when the substance containing group V elements includes an antimony source, when the first hydrothermal reaction is performed, the method further includes adding glucose and ethylenediamine to the reaction system, wherein the molar ratio of the antimony source to the glucose is 1:(14-16); the content ratio of the antimony source to the ethylenediamine is 0.135:(18-22) g / ml; And / or, when the substance containing group V elements includes a bismuth source, when performing the first hydrothermal reaction, the method also includes adding PVP and sodium hydroxide to the reaction system, the mass ratio of the bismuth source to the PVP is 0.233:(0.4-0.6), and the molar ratio of the bismuth source to the sodium hydroxide is 1:(18-22).

7. The method for preparing the composite alkaline hydrogen evolution electrode according to claim 6, characterized in that: The temperature of the first hydrothermal reaction is 170-190°C; And / or, the time of the first hydrothermal reaction is 11-24 hours.

8. The method for preparing the composite alkaline hydrogen evolution electrode according to claim 6, characterized in that: The transition metal chalcogenide compound precursor includes a molybdenum source and a sulfur source; And / or, the molybdenum source includes at least one of ammonium molybdate and sodium molybdate, and the sulfur source includes at least one of thioacetamide and thiourea; and / or, the molar ratio of the molybdenum source to the sulfur source is 1:(2.1-2.7); and / or, the molar ratio of the antimony source to the molybdenum source is 1:(8-9); And / or, the concentration of the molybdenum source in the reaction system is 0.04-0.08 mol / L.

9. The method for preparing the composite alkaline hydrogen evolution electrode according to claim 8, characterized in that: The temperature of the second hydrothermal reaction is 170-190°C; And / or, the time of the second hydrothermal reaction is 19-21 hours.

10. A water electrolysis device, characterized in that: The water electrolysis device comprises a cathode and an anode, wherein the cathode comprises the composite alkaline hydrogen evolution electrode according to any one of claims 1 to 4 or comprises the composite alkaline hydrogen evolution electrode prepared by the preparation method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Bismuth oxybromide composite photocatalyst for hydrogen production and preparation method thereof

    CN108311163A

  • Preparation method of tungsten oxide / antimony sulfide heterojunction electrode for photoreduction of carbon dioxide

    CN110026209A

  • Preparation method and uses of MoS2 / BiVO4 heterojunction composite photocatalyst

    CN110560092A

  • Transition metal sulfide composite hydroxide electrode preparation method and application thereof

    CN114921803A

  • Novel Euglena gracilis strain and beta-1,3-glucan production method using the same

    KR102754023B1